Effectiveness of oxytocin massage on breast milk production in postpartum mothers - Anastasia Lina; Asmaurina Pramulya; Efrosina Ludovika Kalista; Agnes Dwiana Widi Astuti; Anjelina Sera; Odilya Firmatary (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: The postpartum period is a crucial period in a mother's life after childbirth, as it involves significant physical and emotional recovery. One of the main causes of postpartum morbidity is breastfeeding problems due to low milk production. Based on the 2023 Indonesian Health Profile from the Ministry of Health, only around 65.5% of mothers successfully breastfeed exclusively for the first six months. Breastfeeding is considered the best method to provide necessary nutrition, which has benefits not only for the mother's health but also for the optimal growth and development of the child. Oxytocin massage therapy is a massage that aims to stimulate the hormone oxytocin. This technique is effective in increasing milk production and release, providing relaxation, reducing stress, and increasing the bond between mother and baby. Purpose: To identify breast milk production in postpartum mothers using oxytocin massage. Method: This experimental study used a post-test control group design. The population was 36 postpartum mothers within 3 hours of delivery. Through purposive sampling, 24 postpartum mothers were selected as respondents, divided into 12 in the intervention group and 12 in the control group. The measurement instrument used was an observation questionnaire on breast milk production, which measured the newborn's urine volume over a 24-hour period (normally 6-8 times a day). A urine volume of 30-50 mg was categorized as good and a urine volume of less than 29 mg was ≥ inadequate. The intervention consisted of oxytocin massage given to postpartum mothers 3 hours postpartum, every morning and evening, for 3 days. Data were analyzed using the Wilcoxon test to determine the effect of oxytocin massage on breast milk production. Results: The average age of respondents was 27.63 years with a standard deviation of ±4.29 years with the majority of respondents being in the 26-30 years age range of 45.8%. Most of the respondents' education level was junior high school, namely 41.7%, and the majority of respondents had a job status as a housewife, namely 62.5%. Based on the Wilcoxon test, pValue=0.02 was obtained, where for the intervention group, those classified as less were 16.7% and those in the good category were 83.3%. While for the control group, those classified as less were 66.7% and those in the good category were 33.3%. Conclusion: Oxytocin massage intervention has an effect on increasing breast milk production in postpartum mothers. Oxytocin massage has been proven effective in increasing breast milk production and shows a significant difference in breast milk volume after oxytocin massage, where breast milk production increases to a greater or smoother flow, thereby ensuring adequate breast milk supply for the baby. Suggestion: It is recommended that health facilities or community cadres educate the public regarding the understanding and benefits of oxytocin massage. This increased public knowledge will contribute to the implementation of early nutritional adequacy programs for toddlers as an effort to prevent stunting.